Plagioneurin B, a potent isolated compound induces apoptotic signalling pathways and cell cycle arrest in ovarian cancer cells - Nordin, N; Majid, NA; Othman, R; Omer, FAA; Nasharuddin, MNA; Hashim, NM (Springer, 2024)
Indexed by WOS/Scopus/ERA